Manejemen Bimbingan Konseling Kelompok di SMKN 1 Pangandaran - Barizah Amalia; Nurhayati Nurhayati; Pitri Pitri; Ihsan Sanusi; Tedy Kurniawan (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to find out how group counseling is implemented at SMKN 1 Pangandaran. The subject of this research is the guidance and counseling teacher at SMKN 1 Pangandaran who is the implementer of group guidance and counseling. Data collection was carried out using qualitative methods using observation, interview and documentation techniques. The results of the research show that the routine group guidance carried out at SMKN 1 Pangandaran is only carried out once a year which is carried out in large class group guidance activities to collect and provide information and direction to students who are interested in continuing their education at the tertiary level. This activity has quite an influence on students' interest in continuing their education, which can be seen from the increasing interest in them from the previous year.